Pulmonary Vein Stenosis: A Rare Disease with a Global Reach - Jennifer Schramm; Sivakumar Sivalingam; Guillermo E. Moreno; Dinh Quang Le Thanh; Kimberlee Gauvreau; Kaitlin Doherty-Schmeck; Kathy J. Jenkins (Children, 2021)
Pulmonary vein stenosis (PVS) is a rare, but high mortality and resource intensive disease caused by mechanical obstruction or intraluminal myofibroproliferation, which can be post-surgical or idiopathic. There are increasing options for management including medications, cardiac catheterization procedures, and surgery. We queried the International Quality Improvement Collaborative for Congenital Heart Disease (IQIC) database for cases of PVS and described the cohort including additional congenital lesions and surgeries as well as infectious and mortality outcomes. IQIC is a quality improvement project in low-middle-income countries with the goal of reducing mortality after congenital heart surgery. Three cases were described in detail with relevant images. We identified 57 cases of PVS surgery, with similar mortality to higher income countries. PVS should be recognized as a global disease. More research and collaboration are needed to understand the disease, treatments, and outcomes, and to devise treatment approaches for low resource environments.